Disaster Risk Assessment and Education in Limau Manis Village, Pauh District, Padang City, West Sumatera: Kajian Risiko Bencana dan Edukasi Kebencanaan di Kelurahan Limau Manis, Kecamatan Pauh, Kota Padang, Sumatera Barat - Fauzan, Fauzan; Abdul Hakam; Bayu Martanto Adji; Rinaldi Ekaputra; Yenny Narny; Aditya Abdi Pratama; Cindy Murdiaman Guci; Amanda Nurra Mulyana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Disaster risk assessment is an integrated mechanism regarding potential hazards, evaluating existing conditions, and providing a comprehensive picture of disaster risk in an area. This disaster risk assessment and disaster education aims to evaluate disaster risk and provide education to provide a deep understanding of the potential and impacts caused by disasters that occur in an area, especially in Limau Manis Village. The method used in this study is to collect primary and secondary data. Primary data is collected by filling out questionnaires and interviews with respondents selected based on their knowledge and experience of disasters that have occurred in the area. This interview focuses on the community's experience with various types of disasters and how the impact of disasters affects their daily lives, infrastructure, and livelihoods. The data collected is then analyzed to identify potential risks and the level of community preparedness. Based on the results of this study, it was found that the potential for high disaster risk is a flood disaster with a disaster risk value of 3.00, followed by earthquakes, landslides, and extreme weather, which are classified as moderate disasters with a risk value of 2.00. The results of this study are expected to help the local government make better disaster management and mitigation plans in the future. This study can be used as a further reference for disaster risk management in other areas with different social and geographical characteristics